2021
DOI: 10.1177/03635465211008655
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effect of an Intra-articular Injection of Losartan on Microfracture-Mediated Cartilage Repair Is Dose Dependent

Abstract: Background: A previous publication demonstrated that the oral intake of losartan promoted microfracture-mediated hyaline-like cartilage repair in osteochondral defects of a rabbit knee model. However, an intra-articular (IA) injection of losartan may have direct beneficial effects on cartilage repair and has not been studied. Purpose: To determine the dosage and beneficial effects of an IA injection of losartan on microfracture-mediated cartilage repair and normal cartilage homeostasis. Study Design: Controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…Contrary to the structural/ composition benefits (e.g., prevention of fibrillations and erosions) of drug treatment on cartilage seen in these previous preclinical studies, there was no robust tissue-level improvement with most SV and LS strategies in this study. However, recent work has shown LS at higher dosages can halt cartilage repair and induce cartilage damage in healthy cartilage (Logan et al, 2021), which somewhat aligns with the deleterious effects of LS strategies in this study. Collectively, these discrepancies could be due to the dosing strategy, joint location (e.g., anterior vs. posterior), joint studied (e.g., elbow vs. knee), type of arthritis (e.g., rheumatoid arthritis vs. post-trauma osteoarthritis), and type of traumatic insult (e.g., trauma, immobilization, chemical, or combinations).…”
Section: Sv and Ls Induces Pleiotropic Effects On Cartilage Biology I...supporting
confidence: 88%
See 2 more Smart Citations
“…Contrary to the structural/ composition benefits (e.g., prevention of fibrillations and erosions) of drug treatment on cartilage seen in these previous preclinical studies, there was no robust tissue-level improvement with most SV and LS strategies in this study. However, recent work has shown LS at higher dosages can halt cartilage repair and induce cartilage damage in healthy cartilage (Logan et al, 2021), which somewhat aligns with the deleterious effects of LS strategies in this study. Collectively, these discrepancies could be due to the dosing strategy, joint location (e.g., anterior vs. posterior), joint studied (e.g., elbow vs. knee), type of arthritis (e.g., rheumatoid arthritis vs. post-trauma osteoarthritis), and type of traumatic insult (e.g., trauma, immobilization, chemical, or combinations).…”
Section: Sv and Ls Induces Pleiotropic Effects On Cartilage Biology I...supporting
confidence: 88%
“…For example, SV is thought to prevent cartilage damage by enhancing chondrogenesis (e.g., increased proteoglycan synthesis) and reducing chondrocyte production of harmful biochemical factors (e.g., inflammatory cytokines and matrix-degrading enzymes) ( Yudoh and Karasawa, 2010 ; Aktas et al, 2011 ). LS appears to provide similar cartilage structure protection in the knee ( Chen R. et al, 2015 ; Huard et al, 2018 ; Utsunomiya et al, 2020 ; Logan et al, 2021 ) but can also accelerate chondrocyte enlargement/hypertrophy in the growth plate ( Chen S. et al, 2015 ). Contrary to the structural/composition benefits (e.g., prevention of fibrillations and erosions) of drug treatment on cartilage seen in these previous preclinical studies, there was no robust tissue-level improvement with most SV and LS strategies in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 and Logan et al. 28 found that when biologically regulated bone marrow stimulation was performed in conjunction to oral losartan intake, the cartilage repair was superior to the control population, resulting in increased hyaline cartilage formation and reduced fibrocartilage formation.…”
Section: Biologicsmentioning
confidence: 99%
“…However, there is concern about potential side effects of oral administration of the drug, which is an antihypertensive agent. While Logan et al showed that intra-articular injection of losartan promotes cartilage regeneration, they also reported that higher doses of losartan inhibit cartilage regeneration ( Logan et al, 2021 ), suggesting that there is a dose-dependent regenerative response of cartilage to losartan. Furthermore, as a low molecular weight (Mw) drug (Mw < 10,000 Da), losartan can easily diffuse through the interstitium and capillary walls ( Gerwin et al, 2006 ) and is expected to disappear from the joint in a few days.…”
Section: Introductionmentioning
confidence: 99%